C1q nephropathy in India: A single-center study - K V Kanodia; A V Vanikar; R D Patel; K S Suthar; H V Patel; M A Gumber; P R Shah; H L Trivedi (Saudi Journal of Kidney Diseases and Transplantation, 2015)
C1q nephropathy (C1qN) is defined by conspicuous C1q deposits in the glomerular mesangial regions of patients who do not have any evidence of systemic lupus erythematosus (SLE). We present our experience with C1qN over the last three years. In total, 1775 native renal biopsies were reviewed and dominant/co-dominant C1q mesangial deposits in patients with absence of clinical and/or serological evidence of SLE were considered as C1qN. Their clinical profile and renal function status were studied and correlated. C1qN was observed in 11 patients (0.61%), and included eight males and three females; the mean age was 36.6 years. The most common presentation was nephrotic syndrome. Hematuria was noted in eight patients (72%). The mean serum creatinine was 2.78 mg/dL. Hypertension was seen in two patients (18%). Mesangial proliferative glomerulonephritis (MePGN) was the most common histological pattern, followed by focal and segmental glomerulosclerosis and other lesions. The common codeposits along with C1q were IgM, followed by C3 and others. MePGN had better prognosis than others. To conclude, C1qN was noted in 0.61% of all renal biopsies with bimodal age distribution and may present as podocytopathy or non-podocytopathy. The prognosis depends on the morphological pattern and C1q deposits per se are not prognostic indicators.